Genetics of Animal Health and Disease in Livestock - Castiglioni, Bianca (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Wood surface attributes can be established by examining its several different physical or chemical properties. Differences in the wood surfaces occur between the manufacturing and post-treatment processes as well. Understanding how their unique anisotropic molecular organization, chemical linkages, branching, and other molecular features govern micro- and macroscale accessibility is essential for coating and complex modification processes. It is therefore important for scientific as well as practical reasons to qualify and quantify the effects of wood surface treatments and modifications. Challenges still exist to fully understanding the effect of the numerous applied chemicals and the wide range of treatment processes on wood surfaces.